Constructed Single-Crystal Rutile TiO2 Cluster and Plasmon Synergistic Effect for Dye-Sensitized Solar Cells. (20th October 2015) - Yu, Wenjing; Sun, Weiwei; Liu, Yumin; Mehnane, Hadja Fatima; Liu, Haimin; Zhang, Kun; Cai, Bo; Liu, Wei; Guo, Shishang; Zhao, Xing-Zhong
Abstract: We demonstrate a method for incorporating plasmon metallic nanoparticles in hierarchical rutile TiO2 clusters (RTC) assembled from single-crystal nanospindles. The RTC could efficiently improve the diffusion of the photoelectrons, which can be ascribed to the improvement of the connectivity by bridging the neighbouring microflowers through the single-crystal nanospindles. But not all the nanospindles are tightly interconnected, hence organic colloid has been prepared for post-treatment of the device based on RTC by the generation of TiO2 nanoparticles. When added into Au nanoparticles, localized electric fields can be produced, because Au can excite dye molecules more intensively than incident far-field light. The surface plasmon synergistic effect had been investigated by Uv-vis absorption spectrum of Au@ organic colloid and the relative change of the IPCE. As a result, the cell based on RTC exhibits an overall conversion efficiency of 7.68%, indicating a 17% promotion compared with that derived from commercial P25 (6.58%) which could be ascribed to faster electron transfer of single-crystal nanospindles. With the Au nanoparticles incorporation in RTC, the device achieves a conversion efficiency of 9.15%, resulting in a 11% increase compared to the RTC device post-treated by organic colloid without Au nanoparticles (8.24%), which is attributed to the surface plasmon synergistic of Au nanoparticles.